Stress-Induced Hyperglycemia in General Surgery: a Narrative-Review - Homaee, Sina; Saberian, Farnaz; Atarod, Mohammad Mehdi; Kavan, Sahar (Novelty in Biomedicine, 2025)
Background: Stress-induced hyperglycemia, also known as stress hyperglycemia, occurs after severe stress on the body, such as surgery. Awareness of this condition and its management are essential to reducing complications and mortality in patients after general surgery. This study aimed to review studies conducted on stress hyperglycemia in patients who underwent general surgery. Materials and Methods: This review study investigated the outcomes and management of stress hyperglycemia in general surgery patients. From 2014 to 2024, the keywords “stress hyperglycemia” and “general surgery” were searched in the PUBMED, ELSEVIER, and CENTRAL databases. Results: The incidence of stress hyperglycemia varies between studies but often occurs in more than 20% of patients. Compared with diabetic patients undergoing general surgery, patients with stress hyperglycemia have more severe rates of complications and mortality. Complications of stress hyperglycemia include infection, necrosis, organ damage, and mortality. Stress hyperglycemia can also increase the length of hospital stay. Conclusion: The results of this study showed that stress hyperglycemia was common in people who had general surgery and was linked to a higher risk of complications and death compared to patients who did not have hyperglycemia or diabetes.